Medical and psychological aspects of image of flight formation at unmanned aerial vehicle operator - Kokina, Tatsiana V.; Kuntsevich, Andrei I.; Djakov, Dmitry A.; Fourmanov, Igor A. (Journal of the Belarusian State University. Philosophy and Psychology, 2024)
Flight safety of an unmanned aerial vehicle (UAV) of the state aviation is characterised by its emergency-free applying. The effectiveness of the professional activity of a UAV operator is directly influenced by the success of constructing and executing a flight mission, which in turn depends on the characteristics of the mental regulation of his professional activity. Mental regulation of the operator’s control actions is carried out thanks to the formed holistic image of flight. Understanding of the medical and psychological aspects of the mechanisms of its formation will allow us to highlight the features of mental regulation of the operator’s control actions of a UAV operator to solve the problems of training a UAV operator and optimising his professional activity.
Keywords: flight safety; professional activity; human operator; image of flight; mental regulation; operativeness; effectiveness; spatial orientation